2020
DOI: 10.3390/life10050059
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Influences miRNA Expression in Gonadotroph Pituitary Tumors

Abstract: microRNAs are involved in pathogenesis of cancer. DNA methylation plays a role in transcription of miRNA-encoding genes and may contribute to changed miRNA expression in tumors. This issue was not investigated in pituitary neuroendocrine tumors (PitNETs) previously. DNA methylation patterns, assessed with HumanMethylation450K arrays in 34 PitNETs and five normal pituitaries, were used to determine differentially methylated CpGs located at miRNA genes. It showed aberrant methylation in regions encoding for 131 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition to the miR-3658 pathway, our pathway analysis data in GC cells treated with GLA showed that GLA could activate the SMG1-UPF pathway that functions to downregulate the expression of various essential factors facilitating tumorigenesis by inducing mRNA decay ( 26 , 27 ). The SMG1-UPF pathway is a core part of NMD, a quality-control mechanism that rapidly degrades aberrant mRNAs ( 22 , 23 ). Impairment of NMD-mediated mRNA degradation against oncogenesis is involved in various pathophysiological processes of cancer ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the miR-3658 pathway, our pathway analysis data in GC cells treated with GLA showed that GLA could activate the SMG1-UPF pathway that functions to downregulate the expression of various essential factors facilitating tumorigenesis by inducing mRNA decay ( 26 , 27 ). The SMG1-UPF pathway is a core part of NMD, a quality-control mechanism that rapidly degrades aberrant mRNAs ( 22 , 23 ). Impairment of NMD-mediated mRNA degradation against oncogenesis is involved in various pathophysiological processes of cancer ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since miR-3658 could act as a tumor suppressor microRNA and is downregulated in gastric cancer, we sought to explore the mechanism underlying the restoration of miR-3658 by GLA in GC cells. Cancer-related aberrant methylation is commonly observed in miRNA genes, and the hypermethylation leads to the downregulation of the expression of tumor-suppressive miRNAs in cancer cells (22)(23)(24)(25). To investigate whether DNA methylation is involved in the downregulation of miR-3658 in GC cells, we treated GC cells with 5-Aza-CdR, an S-phasespecific demethylating agent, to induce demethylation.…”
Section: Mir-3658 Is Hypermethylated In Gc Cells and Gla Can Restore ...mentioning
confidence: 99%
“…Methylation is another process that may alter miRNA expression. Genes transcribing inflamma-miRs such as miR-21 and mir-145 have been shown to be hypermethylated in gonadotroph pituitary tumors ( 132 ). A recent review by Pajares et al.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Research showed that DNA methylation and miRNAs have mutual regulation and mutual targeting effects [ 11 , 12 ]. The promoter regions of some miRNAs have CpG islands, and abnormal hypermethylation can cause their low expression, leading to tumorigenesis [ 13 ]. There have also been reports that miRNAs can result in abnormal changes in DNA methylation by targeting DNMT1 and DNMT3 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%